1990
DOI: 10.2307/3053616
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Beholder: Tort Litigants' Evaluations of their Experiences in the Civil Justice System

Abstract: Little is known about the reactions of tort litigants to traditional and alternative litigation procedures. To explore this issue, we interviewed litigants in personal injury cases in three state courts whose cases had been resolved by trial, court-annexed arbitration, judicial settlement conferences, or bilateral settlement. The litigants viewed the trial and arbitration procedures as fairer than bilateral settlement, apparently because they believed that trials and arbitration hearings gave their case more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 37 publications
(43 reference statements)
2
100
1
2
Order By: Relevance
“…For example, Lind, Huo, and Tyler (1994) found a remarkably similar pattern of procedural rankings for European, Hispanic, and African American students in a study of different ways of resolving conflicts. Lind, MacCoun et al (1990) found that procedural fairness had similar effects on litigation ratings effects for white vs. non-white, male vs. female, and high vs. low income litigants. Kulik, Lind, Ambrose, and MacCoun (1996; also see Sweeney & McFarlin, 1997) found that no significant differences in the way male and female tort litigants weighted various criteria in procedural justice ratings.…”
Section: Culture Diversity and Consciousnessmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, Lind, Huo, and Tyler (1994) found a remarkably similar pattern of procedural rankings for European, Hispanic, and African American students in a study of different ways of resolving conflicts. Lind, MacCoun et al (1990) found that procedural fairness had similar effects on litigation ratings effects for white vs. non-white, male vs. female, and high vs. low income litigants. Kulik, Lind, Ambrose, and MacCoun (1996; also see Sweeney & McFarlin, 1997) found that no significant differences in the way male and female tort litigants weighted various criteria in procedural justice ratings.…”
Section: Culture Diversity and Consciousnessmentioning
confidence: 86%
“…Surveys showed that arbitration provided litigants with the same desirable procedural dimensions they wanted from trials: the opportunity to present their case, receive a dignified and respectful hearing, and get a verdict on the merits Lind, MacCoun, et al, 1990). But of course arbitration provides those procedural features more quickly and cheaply than trial.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a significant study in the relative deprivation literature (see Crosby (1976) for an overview) is that of deCarufel and Schopler (1979), who reasoned -among other things -that outcome improvement may be a source of rising expectations, and when these rising expectations are violated by improvements that fail to rise at the same rate, people may be dissatisfied with their improved outcomes (see also Stouffer, Suchman, DeVinney, Star & Williams, 1949). Furthermore, the findings of a study conducted by Lind, Maccoun, Ebener, Felstiner, Hensler, Resnik and Tyler (1990) also emphasize the importance of expectations in the development of fairness judgements. After reviewing these and other studies, Furby (1986) concluded that 'the notion that meeting expectations is central in the definition of justice' (p. 183).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of relational concerns is underscored by studies showing that the relationalinteractional component of procedures is especially important in determining people's responses to the way they are treated (Koper, van Knippenberg, Bouhuijs, Vermunt, & Wilke, 1993;Tyler, 1994;Tyler & Bies, 1990;cf. interactional justice;Bies & Moag, 1986;dignitary concerns;Lind et al, 1990) and that the perceived fairness of procedures may affect people's self-evaluations (Koper et al, 1993;Smith, Tyler, Huo, Ortiz, & Lind, 1998;Tyler et al, 1996).' Whereas procedural considerations have a strong link with relational concerns, outcome considerations, in contrast, relate more to resource-based, or instrumental, concerns (Tyler, 1994(Tyler, , 1997(Tyler, , 1999.…”
mentioning
confidence: 99%